O olhar de Van Gogh pelas lentes de Alain Resnais : uma poética da luz - Feliciano, Gilmara Martins (Universidade Federal de São Carlos, 2017)
This study was instigated by the documentary Van Gogh (1947), by Alain Resnais. The main reason for this analysis was given by the peculiar structure of the short film that had only the painting of Vincent Van Gogh as a source image. This nature allowed us to believe that the filmmaker's intention was to 'make' cinema from plastic pictorial material. And he did so in a dynamic that involved his process of creation and that of the painter, because at the same time that he thought the pictorial image, he conjectured it as cinema. Analyzing the creative movement of the artist the director supposedly evidencedhis own movement. The analysis of the structural transformation experienced by the painting was carried out according to the transcreation studies (Haroldo de Campos), of poetic translation (Roman Jakobson) and the implications of the poetic, phatic and metalinguistic functions in the elaboration of the aesthetic object. For this unique condition Van Gogh we recognize it as a film-essay (Arlindo Machado and Ismail Xavier) that transcends the paradigms of the documentary genre. We also sought to guide our analysis of translation from Jacques Aumont 's three operations: diegetization, narration and psychologization, which allowed us to point out the translation procedures (filming, editing and oralized text) responsible for the transformation of painting into cinema.
Van Gogh's view by the lenses of Alain Resnais : a poetic of light
Keywords: Filme-ensaio; Transcriação; Tradução poética; Alain Resnais; Vincent Van Gogh; Film-essay; Transcreation; Poetic translation; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES PLASTICAS::PINTURA; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES PLASTICAS; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::INTERPRETACAO CINEMATOGRAFICA